New concept of e-I-open and e-I-continuous functions / W.F. Al-omeri, M.F. Md. Noorani and A. Al-Omari - Al-omeri, W.F; Md. Noorani, M.S; Al-Omari, A. (2015)
In this paper, new classes of functions are introduced and studied by making use of e-I-open sets and e-I-closed sets. Relationship between the new classes and other classes of functions are established besides giving examples, counter examples, properties and characterizations